Survival trends for very low and extremely low birth weight infants in the Voronezh Region in 2008 to 2012 - I. V. Voronina (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
The 2008—2012 survival trends were analyzed in very low and extremely low birth weight in the Voronezh Region. The official statistical data of Form No. 32 of the Federal State Statistics Service for Obstetric Facilities in the Voronezh Region and its registry office data on consecutive registration of medical death certificates were examined. In 2008 to 2012, the Voronezh Region showed reduced antenatal losses in the group of very low and extremely low birth weight infants. By 2012, along with an increasing number of live births in a group of extremely low birth weight birth infants, the survival up to 1 year doubled and amounted to as high as 43,4%. That was 92,5% in a group of very low birth weight infants. No deaths were notified among the very low and extremely low birth weight babies after primary hospital discharge. The results of the performed studies suggest that the region exhibited the improved quality of care during pregnancy and labor and care to the newborns in the early neonatal period and the increased levels of nursing care for low birth weight infants during the first months of life.